Dominância fiscal : uma investigação empírica sobre o caso brasileiro no período de 2003 a 2014 - Hehr, Deyvid Alberto (2017)
Economic stabilization, in the 1990s, and utilization of an economic tripod, after 1999, represents the end of a delicate chapter in Brazilian history. Ever since, it was necessary the existence of a certain agreement between monetary and fiscal politic, in order to maintain under control a variety of economic indicators. However, this reciprocity (in economic politic) starts discussions about the real government orientations when it comes to define its priority on this subject: are the fiscal variables priorized, and then, determined, forcing monetary variables to adjust themselves, or the opposite? The answer to these questions emerge from the fiscal dominance discussion. This paper intends to empiric verify, using econometric modeling VAR and event study, if there is fiscal dominance or monetary in Brazilian economy and whether the effectiveness of monetary politic has changed in the transition from Lula's government to the Dilma government. The result was inconclusive for the Lula government and indicated fiscal dominance in the Dilma government. There was still no change in the efficiency of the monetary politic.